Economics of Feeding Rice DDGS and Mixture of Wheat Straw and Groundnut Straw to Growing Crossbred Heifers (Indian Journal of Animal Production and Management, 2024)
Feeding of growing heifers is generally ignored by the farmers as they do not want to spend their  limited recourses during their non-productive growing phase. This deprives heifers of essential  nutrients. Present study was planned on twenty-four HF×Kankrej heifers (avg. BW=116.13±4.74kg)  and conducted for 168 days to note the effect of feeding rice DDGS and mixture of wheat straw and  groundnut straw on feeding cost and feed efficiency. Three different concentrates containing 0%,  20% and 40% rice DDGS (RDDGS) were offered to T1, T2 and T3 group heifers, respectively. Under  each group half of the heifers were offered wheat straw and another half a mixture of wheat straw  (50%) and groundnut straw (50%). The protein requirement of heifers was fulfilled as per ICAR (2013)  feeding standards. Cost of feeding under different treatments was calculated from the records of daily  feed consumption and by considering the procurement cost of feeds and fodders. The recorded data  was analyzed by RBD factorial design. Daily feed cost (₹/head/d) reduced linearly and significantly  (p
Keywords: RDDGS; Groundnut straw; Feed cost; Feed efficiency; Growing heifers